Influencing through Language: Skincare Advertising Discourse on Instagram - Fatimah Hidayahni Amin; Seny Luhriyani Sunusi; Amra Ariyani; Geminastiti Sakkir; Nur Ainun Rahmat (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines the linguistic strategies employed in Instagram skincare advertisements and their role in constructing persuasive messages and reinforcing dominant beauty ideologies. The study adopts a qualitative method through Critical Discourse Analysis (CDA), utilizing Fairclough’s three-dimensional framework: textual analysis, discursive practice, and social practice. Data were collected purposively from five Instagram posts by prominent skincare brands, selected based on relevance and audience engagement. The analysis reveals the use of imperatives, emotive vocabulary, structured narratives, and authoritative tone to build trust, appeal to emotions, and promote aspirational beauty ideals. These linguistic choices contribute to a discourse that equates beauty with confidence, self-worth, and social acceptance. The study identifies how these advertisements implicitly link consumption with self-improvement, positioning skincare not merely as a product but as a lifestyle necessity. The findings suggest that skincare advertisements on Instagram function not only as marketing tools but also as ideological texts that shape consumer identity and perpetuate societal norms regarding beauty and self-care. This study contributes to the growing body of literature on discourse and digital media by highlighting the intersection of language, ideology, and consumer culture in online marketing practices.